Effect of Prenatal Yoga on Lower Back Pain in Third Trimester Pregnant Women - Sumarni; Lestari, Yayuk Puji (Poltekkes Kemenkes Palu, 2025)
Background: Third trimester pregnancy is often accompanied by complaints of lower back pain due to hormonal changes and body mechanics. This pain is experienced by 60–80% of pregnant women in Indonesia. Non-pharmacological treatments such as prenatal yoga are considered effective in reducing pain without risk to the fetus. Objective: to assess the impact of prenatal yoga on lower back pain in pregnant women during their third trimester. Method: A quasi-experimental approach was implemented, utilizing a one-group pre-test post-test design with 28 third-trimester pregnant women at TPMB W Banjarmasin City between June and August 2024, selected through purposive sampling. The prenatal yoga sessions lasted 45 minutes per session over a four-week period, led by a certified midwife. Pain levels were evaluated using the Numeric Rating Scale (NRS) and analyzed through the Wilcoxon Signed Rank Test. Results: Before the intervention, the majority of respondents experienced moderate pain (46.4%) with an average pain scale of 2.32 (SD 0.66). After the intervention, most experienced mild pain (78.6%) with the average pain scale decreasing to 1.21 (SD 0.41). The Wilcoxon test results indicated a statistically significant change p = 0.001 (α = <0.05), between the pre- and post-prenatal yoga conditions. Conclusion: Prenatal yoga has been shown to effectively alleviate the pain of lower back suffered by pregnant women during their third trimester. To strengthen these findings, further studies utilizing a randomized controlled trial approach with a larger sample size are recommended.